Estudo de caso do polo de conciliação e mediação Elias Souza: o polo indígena da comunidade de Maturuca, estado de Roraima - JOSAPHAT, Amaiama Lamarão (Universidade Federal do Pará, 2023)
This Diagnostic Report constitutes the final master's work at the Graduate Program in Law and Development of the Amazon at the Federal University of Pará and is intended for the case study of the Pole of Mediation and Conciliation Elias Sousa, the Indigenous Pole of the Community of Maturuca, located in the State of Roraima, is also the first Indigenous Pole in Brazil. Initially, the report makes a general presentation of the work, discussing the guiding questioning for the development of the research, which is the invisibilization of indigenous legal systems in Brazilian law, and proposes to analyze how the creation of the Polo Indígena de Maturuca took place fundamental for the effectiveness of indigenous legal systems. Methodologically, the research is developed from the interlocution of Law and Anthropology, having as a guide the idea of legal sensibilities developed by Clifford Geertz; as well as the search for foundations on the decolonization of research according to Linda Smith's considerations. From then on, the report advances to a historical context about the invisibility of indigenous peoples since the arrival of colonizers. Next, the report addresses an analysis of the presence and approach to issues inherent to indigenous peoples in the international and national order. Finally, for the final delimitation of the general presentation of the work, the report covers the theoretical foundations referring to legal pluralism and indigenous jurisdictions. After presenting the research, the report proceeds to the case study of the Maturuca Indigenous Pole, having as its starting point the preliminary examination of the spatial context in which the Pole is inserted, that is, the State of Roraima; the performance of the Indigenous Council of Roraima; and the jurisprudential precedents of the Court of Justice of Roraima in the recognition of indigenous jurisdictions. After the factual contextualization of the diagnosis, the report finally proceeds to carry out the case study of the Maturuca Hub, describing how its creation and implementation took place; how was the community's relationship with the local Judiciary, and how this relationship improved with the creation of the Polo; how the community dealt with conflicts before the Polo was implemented and how this treatment was given after its creation; the effects arising from the implementation of the Polo; and the verification of the Polo's autonomy in relation to the Court of Justice of Roraima. Finally, the report lists the analysis of the data collected, with the verification of the experience of the Maturuca Hub as a precedent for the effectiveness of indigenous jurisdictions and the development of mechanisms for affirming these jurisdictions; as well as pointing out the perceived challenges for the effectiveness of indigenous legal systems in the Brazilian legal system.